Diálogo verbo-visual em tirinha e história em quadrinhos : formando leitores no ensino fundamental - Pereira, Nicélia Nunes Azevêdo (2019)
This study, titled Verbal-visual Dialogue in comic strip and comics: forming readers in Elementary School, it aimed to encourage the students of the class A of the 6th grade, Paulo Freire State College, linked to the State Education Network of the State of Sergipe, to the acquisition of reading skills of the genres comics and comic strip. The focus of this intervention is focused on the reading of onomatopoeia, which is very present in the genres of the work, that values the verbal-visual articulation in its composition and its construction of meanings. We seek to explore the Junina theme, which contemplated the stage of the students' final productions , extolling, even more, this work because it is something that is part of the social and cultural daily life in that the students are inserted. In order to do so, a study was necessary based on the theories from the perspective of reading verbal and non-verbal language. Therefore, the research was carried out in the context of the training of readers, with a qualitative and interventionist approach based on the studies of Bakthin (1992; 2003), Dionísio (2007; 2010), Koch e Elias (2015), Leffa (1996), Marcuschi (2008), Ramos (2009; 2014; 2017), Solé (1996), among other authors. From the point of view of classroom practice, the work was structured around a didactic sequence applied in the chosen class, which participated in reading activities and the structural aspects of the two genres in question, in addition to a game. For the execution of all these activities, it was necessary to carry out the simultaneous reading of the verbal and visual languages, constituted of the genres comic strip and comic strip. The final product of this work is a report containing the steps for the development of the didactic sequence, as well as the results achieved as to the compositional aspects of genres and, mainly, the comprehension of the orality character present in the onomatopoeia. The results show that there was a significant advance in the reading of the verbo-visual text, due to the detailed work of the structure of the two genders. Thus, we understand that our didactic sequence serves as an instrument of assistance in the work of the teacher, and can be adapted according to the occasions.